Mainstreaming genomics: training experience of hospital medical officers at the Royal Melbourne Hospital. Issue 2 (25th February 2021) - Huq, Aamira J.; Healy, Lachlan; Gorelik, Alexandra; Forrest, Laura E.; Winship, Ingrid M.
Abstract: The rapid evolution and wide applicability of genomic testing means that medical practitioners outside the field are not appropriately skilled to understand the utility of genomics for their patients. Rotating junior doctors through genomic medicine provides them with the hands‐on experience necessary to understand the complexities in this field. In this study, we analysed the training experience of 12 hospital medical officers who rotated through genomic medicine at the Royal Melbourne Hospital. Here, we demonstrate that immersion in clinical genomics aids in mainstreaming genomics knowledge.